Respuesta :
You can solve this equation by factoring. To factor a quadratic, you need to find two numbers whose product is equal to the c term of the function (in this case-8) and whose sum is equal to the b term (6). In this equation, the factors are 4 and 2 because:
4x2=8
4+2=6
The factored form of this equation is : (x+4)(x+2)=0
Now, you can solve for x by setting each term equal to 0.
x+4=0
x=-4
--------------------------------------------------------------------------------------------------------------
x+2=0
x=-2
A trick for this is to just flip the sign of the the number in the parentheses.
x={-4, -2}
Hope this helps!!